Homogenization of a diffusion process in a divergence-free random field - Oelschläger, Karl (The annals of probability, 1988)
We study the homogenization problem for a diffusion process in a divergence-free random drift field. In particular, in case of a small Gaussian field we derive an asymptotic expansion of the effective diffusion matrix in terms of its spectral density.
Gesehen am 08.06.2018